2006
DOI: 10.1016/j.expneurol.2006.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration and proliferation of astrocytes in the mouse dentate gyrus after pilocarpine-induced status epilepticus

Abstract: Astrocytes are relatively resistant to injury compared to neurons and oligodendrocytes. Here, we report transient region-specific loss of astrocytes in mice early after pilocarpine-induced status epilepticus (SE). In the dentate hilus, immunoreactivity for glial acidic fibrillary protein (GFAP) was decreased, and the number of healthy appearing GFAP-or S100β-positive cells was significantly reduced (≥ 65%) 1 and 3 days after pilocarpine-induced SE. Many remaining GFAPpositive cells were shrunken, and 1 day aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 57 publications
6
46
0
Order By: Relevance
“…These discrepancies may be due to the species-specific susceptibility of astroglia to pilocarpineinduced SE or the difference of neuroanatomical characteristics between rats and mice. Indeed, Borges et al (2006) also reported that astroglial degeneration was not observed in the rat hilus following pilocarpine-induced SE, unlike mouse. Further studies are needed to determine whether astroglial degeneration is differentially expressed in astroglial types located in different regions of the rodent hippocampal complex.…”
Section: Astroglial Loss and Epileptogenesismentioning
confidence: 94%
See 1 more Smart Citation
“…These discrepancies may be due to the species-specific susceptibility of astroglia to pilocarpineinduced SE or the difference of neuroanatomical characteristics between rats and mice. Indeed, Borges et al (2006) also reported that astroglial degeneration was not observed in the rat hilus following pilocarpine-induced SE, unlike mouse. Further studies are needed to determine whether astroglial degeneration is differentially expressed in astroglial types located in different regions of the rodent hippocampal complex.…”
Section: Astroglial Loss and Epileptogenesismentioning
confidence: 94%
“…Therefore, our findings underline the possibility that astroglial loss may play a potential role in epileptogenesis. Borges et al (2006) reported that pilocarpine-induced SE evoked loss of GFAP labeling in the mouse hilus, not in the molecular layer. Therefore, they suggested that the mouse hilar astroglia might be vulnerable to pilocarpine-SE or local neurodegeneration of the hilus.…”
Section: Astroglial Loss and Epileptogenesismentioning
confidence: 98%
“…SE-induced reactive astrogliosis plays a significant role in the aberrant synaptic remodeling of the hippocampus thought to underlie the development of epilepsy (Jorgensen et al, 1993;Niquet et al, 1994aNiquet et al, , 1994bRepresa et al, 1995). Reactive astrocytes that proliferate in response to seizures express several genes that promote neurite outgrowth (Represa et al, 1993;Niquet et al, 1994aNiquet et al, , 1994bStringer, 1996) and the increase in the expression of these genes coincides with both the emergence of mossy fiber sprouting and the period when both GFAP and hippocampal cell proliferation are elevated (Khrestchatisky et al, 1995;Represa et al, 1995;Bengzon et al, 1997;Parent et al, 1997;Borges et al, 2006). An attenuation of seizure-induced astrogliosis in SUP rats may thus indicate a reduced progression of epilepsy following SE.…”
Section: Discussionmentioning
confidence: 99%
“…This is also true for newer antiepileptic drugs, such as gabapentin and pregabalin, which have recently been demonstrated to act on the α 2 -δ subunit of a voltagegated calcium channel, thus attenuating the calcium flux into neurons (Davies et al, 2007;Field et al, 2007;Taylor et al, 2007). Apart from dysfunction of neuronal networks (Holmes and Ben-Ari, 2003), dysfunction of astrocytes has recently emerged as a critical component of epileptogenesis adding an additional layer of complexity to the underlying disease process (Borges et al, 2006;Tian et al, 2005).…”
Section: Introductionmentioning
confidence: 99%